Ocorrência de Hipertrigliceridemia em pessoas vivendo com HIV/Aids, em Belo Horizonte, 2001-2010 - Cassia Cristina Pinto Mendicino (2015)
Introduction: Among the metabolic disorders in persons living with HIV/AIDS (PLHA) associated with the use of antiretroviral therapy (ART), dyslipidemia stands out for their higher incidence, atherogenic capacity and because they are known risk factor for cardiovascular diseases. Dyslipidemias in PLHA have clinical and epidemiological relevance and can be described before and after the initiation of ART (pre- and post-ART). In PLHA non-exposed to ART, dyslipidemia are mainly characterized by early decrease in HDL (high density lipoproteins) cholesterol and increases in triglyceride levels in more advanced stages of the disease. In PLHA on ART dyslipidemias are mainly characterized by increased serum levels of triglycerides. Objective: To estimate the incidence of hypertriglyceridemia and investigate potential associated factors associated. Methods: Non-concurrent prospective study carried out with PLHA, who started ART between 2001 and 2005 in Belo Horizonte (MG). Outcome and exposure variables were obtained from the medical charts of patients on ART who attended three public HIV/AIDS referral centers (Training Center and references in infecto-parasitary Orestes Diniz disorders - CTR / DIP, Eduardo de Menezes Hospital - HEM, and Testing and Counseling Center Holy Family - CTA / SF). It was estimated the proportion and assessed the associated factors with the availability of triglycerides results at the start of ART in the initial sample (initial population). Patients with available triglyceride results (baseline population) were evaluated to estimate the prevalence of hypertriglyceridemia and associated factors in the pre-ART phase. Patients free of hypertriglyceridemia were followed-up until a period of five years to assess the occurrence of new cases of the outcome. Hypertriglyceridemia was defined as the level of triglyceride equal or above 150 mg/dl in the first record of laboratory results. To characterize the distribution of exposure variables absolute and relative frequencies were calculated considering the initial, baseline and follow-up population. To characterize the hypertriglyceridemia event after ART was calculated cumulative incidence, incidence density (100 person-months), the survival time and cumulative risk (Kaplan-Meier method). For the multivariate analysis was used Cox proportional hazards model. The magnitude of the association was estimated by hazard ratio (HR) with 95% confidence interval. The assumption of risk proportionality was assessed by Schoenfeld residue analysis. The analysis was conducted using the R version 3.0.1 software. . Results: From the initial population (n = 247 patients), 100 (40.5%) had available triglyceride results at baseline. White skin color, to have more than four doctor visit/year after starting ART and to attend HEM or CTA-SF were statistically associated with the availability of triglyceride results. At the baseline (n=100 patients), 40 (40.0%) patients had hypertriglyceridemia. Statistically significant associations between the presence of hypertriglyceridemia in the basal sample and the exposure variables were not observed. In the baseline population, 57 patients without hypertriglyceridemia and on ART for at least three months were followed for an average time of 28 months (follow-up population). The cumulative incidence of hypertriglyceridemia was 40.4% (n = 23) and incidence density was 1.4 per 100 person-months. The free time of the event was 47 months (median time). For all populations there was a predominance of individuals below 35 years old, male, white, in stable relationship and living in the metropolitan field of Belo Horizonte. There was also predominant in the number of <4 doctor visits/year after initiation of treatment, the referral service (CTR / DIP), low T lymphocyte CD4 + T count (<200 cells / mm3), presence of disease or clinical signs of AIDS and the initial ART regimen with two analog reverse transcriptase inhibitors nucleoside (NRTIs) and a reverse transcriptase inhibitor non-nucleoside analogue (NNRTI). They were independent predictors of hypertriglyceridemia during follow-up, variables male (RH=3,04; IC95%:1,16-7,97), ART switch (RH=3,34; IC95%:1,29-8,64) and NNRTI use (RH=2,35; IC95%:0,88-6,27). Conclusions: The regular order of triglycerides tests was not common a common practice among health professionals, being these only recorded in the more severe cases, with important variation between health services. The prevalence and the incidence of hypertriglyceridemia were higher to that those found in the literature. The chronic features of ART and the fact that hypertriglyceridemia will occur sometime among PLHA, lipid profile should be monitored before and after the start of antiretroviral regimens.